Faktor Risiko Gejala Penyakit Pernapasan Ispa pada Mahasiswa Fakultas Kesehatan Masyarakat UIN Sumatera Utara - Wahyudi Wahyudi; Alyani Dewi Shabrina; Nazli Ba’iah Kudadiri; Niswah Zhafira Komaruddin; Tia Nurlisa (Lembaga Pengembangan Kinerja Dosen, 2025)
Globally, respiratory diseases contribute to 7% of the disease burden (WHO), with over 500 million cases annually. In Indonesia, upper and lower respiratory disorders rank among the top 10 most frequent illnesses. Acute Respiratory Infection (ARI), a major global health issue and a leading cause of child mortality in developing countries, has a high prevalence in Indonesia (up to 30.97%). ARI symptoms include fever, cough, runny nose, sore throat, shortness of breath, and chest pain. This study aimed to determine the risks (knowledge, smoking exposure, environment) associated with ARI symptoms among students of the Faculty of Public Health, UIN North Sumatra. This was an analytical observational study with a Case-Control design. The sample comprised 84 individuals (accidental sampling). The instrument was an online questionnaire (Google Form), and the data source was primary. Data analysis included univariate, bivariate (Chi-Square), and multivariate (linear regression) analyses. The majority of respondents were female (83.3%), aged 20 (52.4%), with 95.2% having high knowledge of ARI symptoms, which was not significantly associated with symptoms (p=0.064). Exposure to cigarette smoke (p=0.011) and living environment (p=0.006) were significantly associated with ARI symptoms (moderate exposure 50%, high 36.9%; reasonably good environment 71.4%). The most frequent ARI symptom severity was mild (34.5%), followed by moderate (31%), and severe (14.3%). Exposure to cigarette smoke and poor living environment significantly influence the risk of ARI symptoms in students, despite their high knowledge, consequently affecting their quality of life and productivity.